(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The study was conducted at the Central Euphrates Center for Tumors and Histopathologica Lab in AL-Sadr Medical City in Najaf province from 2015-12-1 to 2016-7.12. The study was carried out on 29 women within ovarian tumors to assist to investigate the most common types of ovarian epithelial cancer in women as well as a histological changes in the three most common types of epithelial ovarian cancer . Histological study for serous showed many alteration, like cyst formation from the ovary surface which have papillary projection. These papillae are covered by many epithelial layers with multilayer serous cells have been observed, Psammoma bodies was the important feature in the diagnosis of serous tumor tissue. Mucinous cyst adenocarcinoma show the epithelium covering the surface invagenated to the stromal cortex to form glands. In the Stroma area, cells may vary from Cuboidal to Columnar. In advanced case, these cells may be transformed into large cells filled with mucin. The endometrial tumor is characterized by hemorrhage and fibrosis in the cyst which filled with brown fluid from the previous bleeding. Tumor cell have single layer of cuboidal or columnar cells contains longitudinal basal nuclei, the stromal tissue around the gland characterized by hemorrhage.